Efektivitas Edukasi Kesehatan dalam Meningkatkan Pengetahuan Orang Tua dan Kader Kesehatan tentang Deteksi Dini Kanker pada Anak: Effectiveness of Health Education in Improving Parents' and Community Health Volunteers' Knowledge of Early Childhood Cancer Detection - Kamesyworo, Kamesyworo; Hartati, Sri; Haryant, Eka (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Childhood cancer remains one of the leading causes of mortality from non-communicable diseases among children. Delayed diagnosis is largely associated with limited parental awareness of the early signs and symptoms of childhood cancer. Health education is therefore essential to improve community knowledge and promote early detection. This community service program employed a pre-experimental one-group pretest-posttest design. The intervention consisted of health education on childhood cancer, early warning signs, and the importance of early detection through lectures, discussions, and educational leaflets. A total of 20 parents and community health volunteers participated. Knowledge was assessed before and after the intervention using a structured questionnaire. Data were analyzed descriptively and using the Wilcoxon Signed-Rank Test with a significance level of 5%. The proportion of participants with good knowledge increased from 20% to 50%, while poor knowledge decreased from 45% to 10% following the intervention. Statistical analysis demonstrated a significant improvement in participants' knowledge after the educational program (p < 0.001). Health education effectively improves parents' and community health volunteers' knowledge regarding childhood cancer awareness. Continuous educational programs should be integrated into community health promotion strategies to facilitate early detection and timely referral of children with suspected cancer.